Post traumatic type 1 diabetes mellitus (insulin-dependent): a case report - Karrouri, Rabie (The Pan African medical journal, 2014)
Most researchers have studied the influence of life stress as precipitating the onset of type 1 diabetes, but as the relationship between severe psychological trauma and diabetes has been a rarely studied subject in paediatric age group. Here, we report the case of a 10-year-old Libyan boy, without personal or familial diabetes mellitus history, which is presented to Moroccan medico-surgical field hospital, installed in Tunisia for refugees of the Libyan revolution, for type 1 diabetes appeared immediately after severe psychological trauma.